PENGEMBANGAN NILAI-NILAI ADAT NYADHAR SEBAGI UPAYA MENGURANGI COGNITIVE DISSONANCE PADA MAHASANTRI PUTRA PONDOK PESANTREN IBNU KATSIR - Fauzi, Asrorun Ni'am; Mudafiatun Isriyah; Imaratul Ulwiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to develop Nyadhar traditional values as an effort to reduce Cognitive Dissonance among male students at the Ibnu Katsir Islamic Boarding School. Cognitive Dissonance is mental discomfort that occurs when a person has beliefs or values that conflict with their actions or choices. In the context of Islamic boarding schools, this incongruity can affect the mental well-being and consistency of students' behavior. Through a qualitative approach, this research identifies and applies the values of the Nyadhar traditional spiritual tradition rooted in local wisdom as part of the santri development program. It is hoped that values such as togetherness, obedience to teachers, and simplicity can help students deal with internal conflicts between religious values and the demands of modern life. The research results show that integrating Nyadhar traditional values in the daily lives of students can reduce the level of Cognitive Dissonance, increase emotional balance, and strengthen their spiritual identity.